DETEKSI KEBOCORAN CAIRAN LIQUOR DENGAN PEMERIKSAAN SPECT/CT SISTERNOGRAFI RADIONUKLIDA - Kharisma Perdani Kusumahstuti; David Siahaan; Rian Hidayatullah; Achmad Hussein Sundawa Kartamihardja (Faculty of Medicine Universitas Mataram, 2022)
Radionuclide cisternography is often used to prove the presence of cerebrospinal fluid leakage from the nose or ears and to localize the location of the leak. Whether the leak is active or not at the time of examination greatly affects the results of the radionuclide examination. We report a rare study case in a female patient 56 years old, who had the main complaints of nasal discharge, apathy, and weakness. The discharge is mainly felt when the patient is sitting. The patient had a history of transsphenoidal surgery for removal tumor at the epiphyses. Cisternography examination was carried out at the Department of Nuclear Medicine and Molecular Theranostic to confirm a liquor leak in the patient. Imaging was performed at 1.3.6 hours after intrathecal 99mTc-DTPA injection. There is an increase in radioactivity in the nasal area, especially on the 3 hour image. SPECT / CT fusion imaging provides the exact location of the liquor leak at the sphenoid area. The nasal tampon to blood serum ratio is 4: 1. Therapy for the patient is surgery to re-seal the leak.